Rattus norvegicus - Amr, Zuhair S.; Abu, Mohammad A.; Qumsiyeh, Mazin; Eid, Ehab (Zenodo, 2018)
Rattus norvegicus (Berkenhout, 1769) Common name: Norway rat or Brown rat. Diagnosis : Larger more robust rat, head body length about 380 mm, and tail 175 mm. The color is solid grayish brown above and below (Figure 76). Similar to R. rattus , but the tail is shorter than head and body length. Tail also with distinct epidermal scales. Six pairs of mammae. Large and very elongated skull, with parallel tempoparietal ridges. Tympanic bullae small and only little inflated. First upper molar without an anterolateral cusp (Figure 77). Localities: ‘ Ammān, Jarash, Irbid. Habitat: This species is associated with farm buildings in rural areas. Refuse tips, sewer systems, hedges and field margins are also suitable habitats for the brown rat. Biology: This is one the most prolific mammals. Females become sexually mature when they reach 8 to 12 weeksold. Gestation periodlasts for 21 and 23 days.It is possible to have 13 litters per year, each with seven to nine newborns.The Norway ratlive in groups, with a dominant male who gains priority access to food, water and resting sites. Remarks: This species may have been introduced long time ago to the Middle East. It is not as common as R. rattus and did not establish itself very well in our area. The Norway rat can live in close quarters with humans in buildings, trash filled streets, sewer systems, grain bins and stock feeding areas. Its introduction to our area is not known, and it may have gained entrance through commercial shipping after establishment of the ‘ Aqaba Sea port in the early fifties. No direct threats are observed. Published as part of Amr, Zuhair S., Abu, Mohammad A., Qumsiyeh, Mazin & Eid, Ehab, 2018, Systematics, distribution and ecological analysis of rodents in Jordan, pp. 1-94 in Zootaxa 4397 (1) on pages 67-68, DOI:10.11646/zootaxa.4397.1.1, http://zenodo.org/record/1202783